Fatal Enterococcus durans aortic valve endocarditis: a case report and review of the literature. (8th June 2012) - Vijayakrishnan, Rajakrishnan; Rapose, Alwyn
Abstract : Most enterococcal endocarditis is caused by Enterococcus faecalis and Enterococcus faecium. Enterococcus durans is a rare member of non-faecalis, non-faecium enterococcal species and is found in the intestines of animals. E durans endocarditis is a very rare infection—only two cases of endocarditis in humans have been reported in the literature—and usually associated with good outcomes when treated with appropriate antibiotics. We report the first case of fatal E durans endocarditis. This patient had end-stage liver disease with associated compromised immune status that likely contributed to the progression of disease in spite of appropriate antibiotic coverage and clearance of bacteraemia.